Systemic consequences of strokes - Pruszyński, Jacek J. (Przewodnik Lekarza/Guide for GPs, 2008)
Because of their prevalence, strokes are one of the main medical problems that burden not only the patient but also the people taking care of him/her, as well as indirectly – due to the costs of medical and social help – the whole of society. In developed countries stroke is the main cause of physical disability. Even if the stroke itself (because of its peculiar dynamic clinical picture and the speed of accumulation of symptoms) is a process which restricts itself to a relatively short period of time, the after-effects and complications can accompany patients for the rest of their lives. This article outlines selected systemic consequences of strokes, putting strong emphasis on: infection, circulatory disturbances, pressure sores, deep venous thrombosis and pulmonary artery embolism, hyperglycaemia, dysphagia and bone fractures.